Formulation and Evaluation of Solid Lipid Nanoparticle Containing Silver Sulfadiazine for Second and Third Degree Burn Wounds and its Suitable Analytical Method Development and Validation - Mastiholimath, Vinayak Shivamurthi; Valerie, Coutinho Tracy Whitney; Mannur, Vinodkumar Shrishailappa; Dandagi, Panchaxari Mallappa; Gadad, Anand Panchaxari; Khanal, Pukar (Indian Journal of Pharmaceutical Education and Research, 2020)
Aim: The main aim of this research work was to formulate, characterize and evaluate solid lipid nanoparticles containing Silver sulfadiazine. Materials and Methods: Solid lipid nanoparticles were prepared by hot homogenisation technique using Glycerol distearate, Tween 80 and Millipore water. These nanoparticles were then incorporated into a gel using Carbopol and trietnanolamine Optimised formulation was chosen according to its particle size, as it was for topical use. Various different evaluation parameters like viscosity, spreadability, drug content, pH were carried out. Results and Discussion: The in vitro drug release study was performed for 12hrs and the optimised formulation (F4) gave best results. Antimicrobial studies all four formulation carried out and F4 gave better results than the other formulations. The gel drug content was analysed by HPTLC. All the physical parameters were in acceptable limit of pharmacopoeial specifications. A simple, precise, accurate and high performance thin layer chromatographic method was developed for estimation of Silver Sulfadiazine (SSD) which was prepared as a dosage form. The separation was performed out on Merck HPTLC aluminium plates of silica gel G60 F254, (20 x 10cm) with 250μm thickness using n-propanol:25% ammonia (7:3v/v) as mobile phase the wavelength was found to 266nm the drug resolved satisfactorily with Rf 0.451. The calibration plot gave good linear relationship with R2 value of 0.9988 in the concentration range of 0.2 to 1.2μg/ml for SSD.
Keywords: Analytical method; Burn wounds; HPTLC; Silver sulfadiazine; Solid Lipid; Nanoparticles